La fragilité d’un pays qui se développe en ignorant la variabilité pluviométrique : une réflexion sur le chaos dû à la pluie au cours de l'hiver 2000/2001 dans la zone de Porto - Monteiro, Ana (2001)
Evaluating the exceptionality of the Autumn/Winter 2000-2001 rainfall period at the north and centre of Portugal we pretend, with this contribution, to make a reflection concerning the risk of created/increased by the recent planning options in urbanised areas. The difficulties in understanding the natural phenomena and, in this study case, the absence of knowledge about the intense rainfall probability caught people and politicians unprepared to deal with a dramatic sequence of serious acidents. Besides knowing that from November 2000 to March 2001, the rain occurred in 83% of the days (134 days), making the highest accumulated total of rain since 1900 and that January and March were the most humid of the century, it’s important to question ourselves if all the catastrophic consequences couldn’t be avoidable if the planning policy incorporates the knowledge of the climatic context of this region.